The Landscape of Movement Control in Locomotion: Cost, Strategy, and Solution - Croft, James L.; Schroeder, Ryan T.; Bertram, John E. A. (Frontiers in Psychology, 2019)
Features of gait are determined at multiple levels, from the selection of the gait itself (e.g. walk or run) through the specific parameters utilized (stride length, frequency, etc.) to the pattern of muscular excitation. The ultimate choices are neurally determined, but what is involved with that decision process? Human locomotion appears stereotyped not so much because the pattern is predetermined, but because these movement patterns are good solutions for providing movement utilizing the machinery available to the individual (the legs and their requisite components). Under different circumstances the appropriate solution may differ broadly (different gait) or subtly (different parameters). Interpretation of the neural decision making process would benefit from understanding the influences that determine the selection of the appropriate solution in any set of circumstances, including that of normal conditions. In this review we survey an array of studies that point to energetic cost as a key input to the gait coordination system, and not just an outcome of the gait pattern implemented. We then use that information to rigorously define the construct proposed by Sparrow and Newell (1998) where the effects of environment, organism and task act as constraints determining the solution set available, and the coordination pattern is then implemented under a pressure for energetic economy. Environment is defined in terms of affordances based on the ecological psychology definition of the concept and organism is defined as classic morphology and physiology based capabilities. We rely on a novel conceptualization of task that recognizes that the task goal needs to be separated from the mechanisms that achieve the goal if the motivation behind the selection of the mechanism strategy is to be exposed and understood. This reformulation of the Sparrow and Newell construct is then linked to the proposed pressure for economy by considering it as an optimization problem, where the most readily selected gait strategy will be that which achieves the task goal at (or near) the energetic minimum.